Students' Computer Value Belief and Perceived Parental Support among VSU-Isabel Students during COVID-19 Online Classes - Aunzo, Rodulfo (Interdisciplinary Research Review, 2025)
The COVID-19 pandemic has necessitated a shift to online learning for tertiary students in the Philippines. Therefore, this research investigates the association between students' computer value beliefs (CVB) and their perceptions of parental support (PPS). This inquiry adopts a correlational research approach to establish the relationship between these variables. The study involved selecting 687 college students in their first to fifth years at VSU-Isabel, utilizing a convenience sampling technique. The findings of this research study indicate that students generally recognize the value of computers for their education. However, their perceptions of parental support remain somewhat ambivalent. Furthermore, the study identifies a noteworthy and moderately positive correlation (r = 0.506, p < .01) between students' computer value beliefs and their perceptions of parental support during the "new normal" brought about by the pandemic. These findings underscore the importance of educational initiatives, such as webinars, to inform parents about the significance of computers in the current educational landscape. Such efforts can contribute to developing more robust perceived parental support among students in this evolving educational environment.